Proceedings of the 5th International Conference on Education and Technology (ICET 2019) 2019
DOI: 10.2991/icet-19.2019.133
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Peer Social Support to the Hardiness of Students

Abstract: Hardiness is a characteristic of students who are able to be positively oriented and configure a stressful experience so that students can survive and develop. The existence of peers in the boarding school environment has an important role as social support in shaping the characteristics of the hardiness of students. The purpose of the study was to find out the contribution of peer social support to the hardiness of students in the grade XI of MA Manarul Huda Boarding School Tasikmalaya academic years 2018/201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(9 citation statements)
references
References 2 publications
1
8
0
Order By: Relevance
“…Furthermore, the research demonstrates a relationship between peer social support and academic hardiness in high school students. This is in line with previous studies by Ganellen and Blaney (1984), Kustiawati et al (2019), andOktavia et al (2019), which suggest a connection between peer social support and hardiness. However, there are variations in results across different indicators.…”
Section: The Influence Of Self-esteem and Peer Social Support On Acad...supporting
confidence: 93%
See 4 more Smart Citations
“…Furthermore, the research demonstrates a relationship between peer social support and academic hardiness in high school students. This is in line with previous studies by Ganellen and Blaney (1984), Kustiawati et al (2019), andOktavia et al (2019), which suggest a connection between peer social support and hardiness. However, there are variations in results across different indicators.…”
Section: The Influence Of Self-esteem and Peer Social Support On Acad...supporting
confidence: 93%
“…Ganellen and Blaney (1984) found that social support was related to two aspects of hardiness: commitment and challenge. In contrast, Kustiawati et al (2019) found that peer social support was related to hardiness more broadly. .000 Notes.…”
Section: The Influence Of Self-esteem and Peer Social Support On Acad...mentioning
confidence: 77%
See 3 more Smart Citations